Boson peak in covalent network glasses: Isostaticity and marginal stability - Hideyuki Mizuno; Tatsuya Mori; Giacomo Baldi; Emi Minamitani (Proceedings of the National Academy of Sciences, 2026)
The excess vibrational states relative to the Debye model of solids, referred to as the boson peak (BP), are a key feature of glasses and amorphous materials. These excess states underlie anomalous thermal properties such as excess specific heat and low thermal conductivity, as well as mechanical characteristics such as nonaffine elasticity and brittle plasticity. Despite its importance, understanding of the BP remains limited in covalent network glasses. The most promising concepts are isostaticity and marginal stability, which have been established in theories of rigidity percolation and the jamming transition. While these concepts, supported by extensive data, account for the BP in packing-based glasses, comparable explanations have not yet been demonstrated for covalent network glasses. Here we study silica glass, a prototypical covalent network glass, using molecular dynamics simulations. We show that the BP in silica glass is governed by near-isostatic constraints and marginal stability, supporting the universality of these concepts across diverse glassy systems. Furthermore, we reveal that these principles manifest as a wavenumber-independent band in the dynamical structure factor, and we demonstrate agreement with inelastic X-ray scattering data. Our results provide an experimentally testable framework for deciphering the BP and for refining the interpretation of scattering data in amorphous materials.